Frequency of physical inactivity and insufficient sleep, and their mixed effects on academic achievement in ethnic minority students: A matched case-control study in a dental school - Carlos Martín Ardila; Ángela María Gómez-Restrepo (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Ethnic minorities are underrepresented in health sciences programs in various nations. Furthermore, there is no known research studying the occurrence of physical inactivity (PI) and insufficient sleep (IS), and their effects on academic achievement (AA) in ethnic minority students (EMS) in higher education. OBJECTIVE: The objective of this study is to explore the occurrence of PI and IS, and their independent and mixed effects on AA in EMS of a dental school. MATERIALS AND METHODS: Thirty EMS and sixty non-EMSs were matched (1:2) in this case-control study. It was utilized as an administrative dataset that stores register related to the students. Moreover, the grade point average was considered an indicator of AA. Logistic regressions models were run, expressed in odds ratios, complemented by confidence intervals (CIs) of 95%. RESULTS: A total of 73% and 60% EMS were PI and slept insufficiently, respectively. The groups presented statistically significant differences (P < 0.0001) in physical activity, sleep, and AA, with inferior values for EMS. All unadjusted models showed that PS, IS, and low AA were strongly associated with EMS, demonstrating their independent effect. After controlling for PI and IS, the multivariate model for AA and EMS increased odds by 6.5 times (95%CI: 1.8-23;), indicating that EMS is strongly associated with low AA. Besides, PI and IS were also statistically significant higher (< 0.0001) in the model, demonstrating their mixed effect. CONCLUSIONS: This study found a higher occurrence of PI and IS in EMS. Besides, independent and mixed effects of these variables on low AA in EMS were very significant.